Clustering players for load balancing in virtual worlds. (29th December 2008) - Rieche, Simon; Wehrle, Klaus; Fouquet, Marc; Niedermayer, Heiko; Teifel, Timo; Carle, Georg
In current Massively Multiplayer Online Games (MMOGs) the distribution of load is not distributed dynamically. But players tend to concentrate in certain regions of the game world and cause overload conditions. Therefore we propose the use of structured Peer-to-Peer technology for the server infrastructure of the MMOGs to improve the reliability and scalability. Previous work segmented the game work into rectangular areas but often split a group of players to different servers. This work presents a cluster-based P2P approach, which is able to dynamically adapt to the current state of the game and handle uneven distributions of players. We show through simulation, also with traces from real online games, that the cluster-based approach performs better than the previous P2P-based system.